If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (w)(2w + -1) = 91 Reorder the terms: w(-1 + 2w) = 91 (-1 * w + 2w * w) = 91 (-1w + 2w2) = 91 Solving -1w + 2w2 = 91 Solving for variable 'w'. Reorder the terms: -91 + -1w + 2w2 = 91 + -91 Combine like terms: 91 + -91 = 0 -91 + -1w + 2w2 = 0 Factor a trinomial. (-13 + -2w)(7 + -1w) = 0Subproblem 1
Set the factor '(-13 + -2w)' equal to zero and attempt to solve: Simplifying -13 + -2w = 0 Solving -13 + -2w = 0 Move all terms containing w to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + -2w = 0 + 13 Combine like terms: -13 + 13 = 0 0 + -2w = 0 + 13 -2w = 0 + 13 Combine like terms: 0 + 13 = 13 -2w = 13 Divide each side by '-2'. w = -6.5 Simplifying w = -6.5Subproblem 2
Set the factor '(7 + -1w)' equal to zero and attempt to solve: Simplifying 7 + -1w = 0 Solving 7 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -1w = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -1w = 0 + -7 -1w = 0 + -7 Combine like terms: 0 + -7 = -7 -1w = -7 Divide each side by '-1'. w = 7 Simplifying w = 7Solution
w = {-6.5, 7}
| (w)(2w^2)=91 | | 8v^2+10v-3=0 | | x/20-5=-4 | | -4(-5-3x)=116 | | 25x^2+30=55 | | B-24.6=5.1b | | 2+x/4=-2 | | 2(5.5)+3(5.5+1.5)= | | 2(4-20)=8(x-5) | | 6x+52=2x+24 | | B-24.6=5 | | 4p-15=1 | | x/5-7=x+6/3 | | 3+12=9y+4-8y | | 16=x/11 | | 1/x+3/7=5/x | | 5(x+8)=0 | | 7x+3(2x)=39 | | 4(2x-1)-2(3x+5)=x+4 | | 2/3+x^2-5/6+x=0 | | 12+d+8+4d= | | 2/3x^2-5/6x=0 | | 2/3x^2-5/6x | | 5/11x5/12 | | 2(1+5x)=82 | | 24=4x-10 | | 10(r-6)/10r | | -b+2=-.5 | | 5+9x=1+3x | | 6x+3x+x= | | 12y+6-11y=14.5 | | 8x+2x=40 |